Effect of Participatory Health Promotion Initiative on Tobacco Use among Adolescents: A School-Based Quasi-Experimental Pilot Study from Central India - Shrinidhi S Datar; Priyadarsh Ture; Abhishek V Raut; White Coat Army Students Author Group (Wolters Kluwer Medknow Publications, 2019)
Introduction: Prevalence of noncommunicable diseases (NCDs) is increasing rapidly in developing countries like India. The commonly attributable modifiable risk factors of NCDs include raised blood pressure (13%), tobacco use (9%), physical inactivity (6%), and obesity (5%). This quasi-experimental study with a pre-post design was conducted with an objective to assess the effect of Participatory Health Promotion initiative (PHPI) on tobacco use among adolescents. PHPI included distribution of personalized health card, tobacco-tar experiment demonstration, use of body mapping technique to emphasize hazards of tobacco on different body organs, and sensitization in small groups. Methods: Baseline tobacco use and health risk assessment were conducted by adapting WHO ASSIST tool among 200 students who were randomly selected from a secondary high school. All students in the school were then exposed to the PHPI. The postmeasurement was done among another 200 randomly selected students after 3 months. Results: The number of current tobacco users reduced from 29 (14.5%) in the baseline to 9 (4.5%) in the postmeasurement with a P < 0.001. Participants with a moderate risk of health hazard due to tobacco use decreased from 21 (72.4%) in the baseline to 5 (55.6%) in the postmeasurement. Students with a higher risk of health hazard because of tobacco use decreased from 6 (20.7%) in the baseline to 1 at the postmeasurement (11.1%). Conclusion: The school-based PHPI was effective in reducing the number of tobacco users among the Indian adolescents.